Nälkävuodet 1867-1868 - Jussila, Tuomas; Rantanen, Lari (Suomalaisen Kirjallisuuden Seuran toimituksia, ISSN 0355-1768, 2018)
English abstract.
Keywords: historia : Suomi : 1800-luku; nälkä; nälänhätä